Legal Problems in Managing Environmental Activities in Iraq's Oil and Gas Industry - Jaafar Naser Abdulridha; Sattar Jabbar Zayer (Rechtsidee, 2024)
General Background: Oil and gas production is a cornerstone of Iraq's economic development. Specific Background: However, this industry significantly impacts the environment, necessitating the implementation of environmental sustainability systems during production. The current governmental framework, while somewhat organized in hydrocarbon production, lacks a unified law that comprehensively regulates all aspects of oil and gas production, including environmental preservation. Knowledge Gap: Existing environmental laws suffer from poor coordination, complicating the regulation of environmental activities to meet the minimum global standards set by the United Nations Sustainable Development Agenda 2030. Aims: This article aims to analyze the environmental protection measures undertaken by Iraqi administrative authorities in the oil and gas sector, examining the public administration, technical aspects, and related institutions' efforts to mitigate pollution. Results: The study reveals that despite some organized efforts, the regulatory framework is insufficiently coordinated, hindering effective environmental protection. Novelty: The article highlights the chaotic regulatory environment and underscores the urgent need for a unified legal framework and better-coordinated environmental laws. Implications: The findings suggest that Iraq must adopt advanced technologies and modern policies to improve environmental sustainability in its oil and gas industry, aligning with global environmental standards. Proposed measures include enhanced regulatory coordination and the integration of innovative technologies to reduce pollution levels in hydrocarbon production processes.Highlights: Lack of a unified law in hydrocarbon production regulation. Poor coordination of existing environmental laws. Need for advanced technologies to reduce pollution in the oil and gas industry. Keywords: Environmental Protection, Pollution, Regulation, Oil, Gas